Exploring oxidative stress pathways in Geobacter sulfurreducens: the redox network between MacA peroxidase and triheme periplasmic cytochromes - Portela, Pilar C.; Morgado, Leonor; Silva, Marta A.; Denkhaus, Lukas; Einsle, Oliver; Salgueiro, Carlos A. (Frontiers in Microbiology, 2023)
The recent reclassification of the strict anaerobe Geobacter sulfurreducens bacterium as aerotolerant brought attention for oxidative stress protection pathways. Although the electron transfer pathways for oxygen detoxification are not well established, evidence was obtained for the formation of a redox complex between the periplasmic triheme cytochrome PpcA and the diheme cytochrome peroxidase MacA. In the latter, the reduction of the high-potential heme triggers a conformational change that displaces the axial histidine of the low-potential heme with peroxidase activity. More recently, a possible involvement of the triheme periplasmic cytochrome family (PpcA-E) in the protection from oxidative stress in G. sulfurreducens was suggested. To evaluate this hypothesis, we investigated the electron transfer reaction and the biomolecular interaction between each PpcA-E cytochrome and MacA. Using a newly developed method that relies on the different NMR spectral signatures of the heme proteins, we directly monitored the electron transfer reaction from reduced PpcA-E cytochromes to oxidized MacA. The results obtained showed a complete electron transfer from the cytochromes to the high-potential heme of MacA. This highlights PpcA-E cytochromes' efficient role in providing the necessary reducing power to mitigate oxidative stress situations, hence contributing to a better knowledge of oxidative stress protection pathways in G. sulfurreducens.